Design Considerations for Integrating Twitter into an Online Course - Rohr, Linda Elizabeth; Costello, Jane; Hawkins, Thomas (International Review of Research in Open and Distributed Learning, 2015)
While the use of Twitter for communication and assessment activities in online courses is not new, it has not been without its challenges. This is increasingly true of high enrolment courses. The use of a Twitter Evaluation application which leverages a Learning Management System’s (LMS’s) application programming interface (API) provides a solution which reduces the administrative overhead associated with tracking students’ Tweets and allows the grader to focus on the assessment of the Tweets’ quality. Such an application and how it improved the assessment process of grading Tweet events is described. In addition to the technological considerations, the soundness of the Twitter learning design in the course impacts the effectiveness of the Tweet events for learning and enhancing the much needed online social presence. Learning design considerations are also discussed.